Pengaruh dimensi pembangunan berkelanjutan terhadap kualitas lingkungan hidup di Provinsi Daerah Istimewa Yogyakarta - Nugroho, Sulistiawan Fajar; Pangaribowo, Evita Hanie (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Sustainable development in a region has a balance between its dimensions, which will affect successful development. Successful sustainable development is proven by improving environmental quality. However, implementing existing sustainable development has not yet to produce maximum output. This research aims to determine the influence of sustainable development dimensions on the environmental quality in each regency/city of Daerah Istimewa Yogyakarta. The research results show that the highest achievement on the social dimension index is Kota Yogyakarta, the economic dimension is Kulon Progo, the environmental dimension is Sleman, and the legal and governance dimensions are Kulon Progo. In addition, the typology of environmental quality through the environmental budget and agricultural PSTK approach shows that Kulon Progo and Gunungkidul are classified as well-developed typologies. On the other hand, panel data regression analysis using the fixed effect model shows a probability value of 0,000003 so that sustainable development dimensions simultaneously significantly influence environmental quality. Therefore, a balance is needed between the dimensions of sustainable development so that environmental quality improvement can be achieved.